ACCOUNTING SYSTEM SALES ANALYSIS OF CV. AMBASSADOR JAVA TEA INDUSTRY (Tea 2Tang) TEGAL - Wahyuni, Wahyuni (Accounting, 2010)
The purpose of this study was to determine the accounting system cash sales that happened on the CV. Ambassador Java Tea Industry (2 Tang Tea). The problem in this study were (1) how the implementation of Accounting System Sales in the Company CV. Ambassador Java Tea Industry, (2) Is Sales Accounting System which was held on CV. Ambassador Java Tea Industry has been able to present the required information management company, (3) Does the Internal Control System has been implemented by the Company CV. Ambassador Java Tea Industry in the implementation of corporate Sales Accounting System. The method and type of data used in data collection that is kind of secondary data consist of documentation methods and methods of basic theory. Technique or method of sampling in this study is a joint CV. Ambassador Java Tea Industry with over 1-month observation period starting December 1, December 25, 2008. While the data analysis techniques used include (1) descriptive: company profile, sales accounting system, accounting procedures within the system of cash sales. Test results on CV. Ambassador Java Tea Industry show that has been operating efficiently. This can be seen from cash sales report showing the number of orders or an increase in demand by consumers. Keywords: Systems, Methods, Accounting, Sales